Peningkatan Kemampuan Mengenal Warna Melalui Metode Bermain Bendera Pada Anak Usia Dini di TK Aba Ciamis - Sri Wahyuni, Tyas; Hasna Luthfiyah, Ghina; Khotimah, Husnul; Mustakimah, Risma; Santika, Santika; Azahra, Tarisa; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract   Introduction : Early childhood education is the level of education before the basic level which provides guidance to children from birth to the age of six. One of the most important components of cognitive development for children's thinking abilities is cognitive development. Objective: to find out whether or not there is an influence from playing with various types of flags at the Aba Ciamis Kindergarten on children's ability to recognize colors. Method : In an effort to solve the problem of color recognition in early childhood at Aba Ciamis Kindergarten, with a total of 15 participants using observational research methods. The instruments used are various flags and observation sheets carried out on November 30, 2023. Result : The results of research conducted at Aba Ciamis Kindergarten to improve the ability to recognize colors through the flag playing method showed that 0% of children were not yet developing (BB) with a total of 0 students, development was starting to develop (MB) as much as 80% with a total of 12 students, the development is Developing According to Expectations (BSH) as much as 20% with the number of students being 3 people, and the development is Developing Very Well (BSB) as much as 0% with the number of students being 0. Conclusion : The flag playing method can improve children's ability to recognize colors at Aba Ciamis Kindergarten. Children really enjoy playing while learning. To improve children's ability to recognize colors for implementation activities, facilitators must prepare implementation activities and make observations to determine the progress each child has achieved.